2015
DOI: 10.1063/1.4916379
|View full text |Cite
|
Sign up to set email alerts
|

How a short double-stranded DNA bends

Abstract: A recent experiment using fluorescence microscopy showed that double-stranded DNA fragments shorter than 100 base pairs loop with the probabilities higher by the factor of 10 2 -10 6 than predicted by the worm-like chain (WLC) model [R. Vafabakhsh and T. Ha, Science 337, 1101(2012)]. Furthermore, the looping probabilities were found to be nearly independent of the loop size. The results signify a breakdown of the WLC model for DNA mechanics which works well on long length scales and calls for fundamental under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…This controversial finding spurred debate on the characteristic length at which DNA cyclization efficiency deviates from the predictions of the WLC model. Despite much experimental [5,[17][18][19][20][21] and theoretical effort [7,[22][23][24][25][26][27][28][29][30][31][32][33][34][35], a consensus has not yet been established.…”
Section: Dna Cyclizationmentioning
confidence: 99%
“…This controversial finding spurred debate on the characteristic length at which DNA cyclization efficiency deviates from the predictions of the WLC model. Despite much experimental [5,[17][18][19][20][21] and theoretical effort [7,[22][23][24][25][26][27][28][29][30][31][32][33][34][35], a consensus has not yet been established.…”
Section: Dna Cyclizationmentioning
confidence: 99%
“…The cyclization factors were measured to be several orders of magnitude greater than those predicted by the WLC model for DNA lengths below 100 base pairs (bp). This phenomenon implied an increase in dsDNA flexibility, possibly due to a flexible hinge in the form of kinks and bubbles that can form under strong bending 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…A more likely explanation is that the CSO model fails to capture the salient physics at the short segment lengths and needs to be further elaborated to accurately describe the cyclization of such sequences. In support of the latter explanation, it was previously suggested that (especially for fragments shorter than 70 bp) there is a need to consider a kink-able WLC [ 22 , 51 ] and/or melt-able WLC [ 4 , 52 , 53 ] models. Future studies will be needed to evaluate the performance of such models in regards to a large collection of DNA fragments with experimentally measured J factors.…”
Section: Discussionmentioning
confidence: 98%